Kualitas Pelayanan, Harga Dan Lokasi Sebagai Penggerak Kepuasan Di Toko Kue Medan Par Par - Siregar, Rara Astili (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2024)
This research aims to examine the impact of service quality, price, and location on customer satisfaction. The study employs a quantitative approach, utilizing questionnaires for data collection. The independent variables are service quality, price, and location, while the dependent variable is customer satisfaction at Medan Par Par Cake Shop. According to the test results, all instruments were validated as reliable, normal, and accurate. The findings reveal that service quality significantly influences customer satisfaction, accounting for 40.3% of the effect, meaning that for each one-point improvement in service quality, customer satisfaction increases by 0.403. Price also has a significant impact on customer satisfaction, contributing 43.3%, indicating that a one-point increase in price leads to a 0.433 increase in customer satisfaction. Conversely, location shows no significant effect on customer satisfaction, with an influence of just 3.6%, suggesting that a strategic location does not necessarily enhance customer satisfaction at Medan Par Par Cake Shop.